Parameters of the mmp / timp system in assessing the clinical course of pulmonary tuberculoma - D. S. Esmedlyaeva; N. P. Alekseeva; M. Ye. Dyakova; D. V. Karostik; I. V. Grigoriev; E. G. Sokolovich (Бюллетень сибирской медицины)
Aim. To study the parameters of the matrix metalloproteinase (MMP) / tissue inhibitors of metalloproteinase (TIMP) system in assessing the clinical course of pulmonary tuberculoma.Materials and methods. We examined 87 patients (55 men and 32 women), average age 33 [28; 43] years, with a morphologically and bacteriologically confirmed diagnosis of tuberculoma, who received treatment at St. Petersburg Research Institute of Phthisiopulmonology. In all patients, computed tomography of the chest, fiberoptic bronchoscopy, and lung function tests were performed. In the blood serum, concentrations of MMP-1, -8, -9, and their tissue inhibitor TIMP-1 were determined using ELISA (R&D Systems, USA), and the activity of α2-macroglobulin (MG) was determined by the enzyme assays. For statistical data processing, Statistica 10.0 and R were used.Results. In the study group, single and multiple tuberculomas were revealed in 37 and 63% of cases, respectively, necrotic areas – in 50% of patients, external respiration disorders – in 48% of cases, and catarrhal bronchitis (CB) – in 77% of cases. Tobacco smokers (TS) were identified in 69% of cases. Significant differences between MMP concentrations allowed us to distinguish four patterns from the characteristics adopted for the clinical and radiological assessment of disease intensity. It was shown that an increase in the levels of MMP-1 and MMP-9 can be a predictor of tuberculoma progression caused by a diffuse process with necrotic areas and bronchogenic dissemination (pattern 1, 2). Changes in the levels of MMP-8, TIMP-1 or MG (pattern 3, 4) were associated with permanent exposure to a non-specific component of inflammation (TS or CB).Conclusion. Changes in the MMP / TIMP system parameters can be used as objective laboratory protein biomarkers to assess the clinical course of pulmonary tuberculoma.